1998
DOI: 10.1111/j.1346-8138.1998.tb02391.x
|View full text |Cite
|
Sign up to set email alerts
|

Suplatast Tosilate (IPD®), a New Immunoregulator, Is Effective in Vitiligo Treatment

Abstract: The major type of vitiligo is considered to be an autoimmune disorder. Anti-melanocyte antibodies are frequently detected in sera of patients with this disease. Interleukin (IL)-4 released from Th2 cells is an important factor in stimulating autoantibody production by B-cells. In this study, seven patients with vitiligo treated with suplatast tosilate (IPD), three showed repigmentation and improvement of their lesions after administration of the drug. IPD halted the continuous spread of the lesions in three of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…A recent report showed that treatment with IPD resulted in diminished infiltration of eosinophils and improved BHR in patients with mild asthma [29]. It should be noted that IPD has beneficial therapeutic effects not only on bronchial asthma, but also on eosinophilic pneumonia, Kimura’s disease and vitiligo [30, 31, 32, 33]. The same mechanism demonstrated in our present study may possibly take place in humans.…”
Section: Discussionsupporting
confidence: 67%
“…A recent report showed that treatment with IPD resulted in diminished infiltration of eosinophils and improved BHR in patients with mild asthma [29]. It should be noted that IPD has beneficial therapeutic effects not only on bronchial asthma, but also on eosinophilic pneumonia, Kimura’s disease and vitiligo [30, 31, 32, 33]. The same mechanism demonstrated in our present study may possibly take place in humans.…”
Section: Discussionsupporting
confidence: 67%
“…Several preliminary studies have reported the efficacy of immunomodulatory drugs, including levamisole, anapsos, isoprinosine, and suplatast tosilate, as repigmenting agents for patients with vitiligo. 8,[14][15][16] Tacrolimus ointment, a novel topical immunomodulatory drug, is used for treatment of atopic dermatitis in both adults and children. In recent studies, tacrolimus has also been reported to induce repigmentation in vitiligo patients.…”
mentioning
confidence: 99%
“…Hence, tofacitinib, a JAK3 inhibitor designed to lower IL-4-related Th2 cytokines, may thus be useful in treating certain cases of refractory vitiligo. Intriguingly, Nihei et al ( 55 ) used IL-4 inhibitors to treat vitiligo patients; most patients had effective control of their cutaneous lesions, and no overtly negative side effects were discovered. This shows the reasonability and scientificity of IL-4 inhibition in treating some vitiligo patients.…”
Section: Discussionmentioning
confidence: 99%